PERBANDINGAN HUBUNGAN SIPIL-MILITER DI INDONESIA PADA MASA ABDURRAHMAN WAHID DENGAN ERDOGAN DI TURKI - Mhd. Alfahjri Sukri (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: This paper aims to compare civil-military relations in Indonesia during Abdurrahman Wahid's (1999-2001) period with Turkey during Erdogan's (2003-2011) by looking at civilian control over the military. The study looks at the differences and similarities between the two countries and the causes of Erdogan's success and Abdurrahman Wahid's failure to control the military. In this research, the author used a qualitative approach. The results showed that there were similarities and differences in civil-military relations between Gus Dur and Erdogan, as seen from civil control over the military. The similarities could bee seen at the beginning of their reign. Abdurrahman and Erdogan had strong civilian control over the military so that they could reduce the military's role in politics with various policies issued. This strong control is also supported by political conditions, political elites, and society. However, there were differences in civil-military relations at the end of the Gus Dur and Erdogan governments. Civilian control over the military weakened at the end of the Gus Dur’s reign which caused him to fall from his position as the President of the Republic of Indonesia, whereas Erdogan’s civilian control over the military was getting stronger. The failure factor for Abdurrahman to strengthen civilian control over the military was a radical change. In contrast to Erdogan who made changes gradually with the support of politics and society.Keywords: Turkey; Indonesia; Abdurrahman Wahid; Erdogan; Civil-Military Relations